The potential roles of dental pulp stem cells in peripheral nerve regeneration - Fu, Jing; Li, Xigong; Jin, Feilu; Dong, Yanzhao; Zhou, Haiying; Alhaskawi, Ahmad; Wang, Zewei; Lai, Jingtian; Yao, Chengjun; Ezzi, Sohaib Hasan Abdullah; Kota, Vishnu Goutham; Hasan Abdulla Hasan Abdulla, Mohamed; et al. (Frontiers in Neurology, 2023)
Peripheral nerve diseases are greatly related to severe fracture, trauma, and tumor surgery, leading to reduced quality of life and impaired physical and mental health. Peripheral neuropathy, as a common long-term complication of severe fracture, trauma, and surgery, could result in reduced living standards and well-being of patients. Human dental pulp stem cells (DPSCs) are neural crest stem cells that provide a novel cell source for nerve regeneration that can be easily extracted from pulp tissue of human permanent and deciduous teeth, with a stronger multidirectional differentiation potential and proliferation capacity than other stem cells. DPSCs can express neurotrophic and immunomodulatory factors, inducing blood vessel formation and nerve regeneration. Therefore, DPSCs possess valuable therapeutic potential in the management of peripheral nerve diseases. With the purpose of summarizing the advances in DPSCs and their potential applications in peripheral nerve disease, this article reviews the biological characteristics of DPSCs and the mechanisms of peripheral nerve regeneration.